The reality of scientific production among faculty members of the University of Sharjah in the light of the coronavirus pandemic: Study applied to a sample of faculty members at the University of Sharjah - El-Shawish, Huda; Al-Hilalat, Khalil (Al-Adab Journal, 2023)
This scientific paper addresses the reality of scientific production of faculty members in the light of the coronavirus pandemic through a study applied to a sample of faculty members at the University of Sharjah. The study highlighting the reality of scientific production of faculty members in terms of scientific and social motivations, focusing on the most important constraints, including the University's infrastructure: technical and several other aspects, and monitoring of the most important catalyst for increasing the scientific production of faculty members in the light of the coronavirus pandemic. This study carried on a sample of 73 of faculty members at the University of Sharjah; using social survey methodology.The most important findings of the study were that the coronavirus pandemic caused difficulty in direct communication between the members of the teaching staff, master and doctoral researchers with an average arithmetic of 2.88 and standard deviation of 0.219.  In addition, the faculty member had a great sense of self-esteem due to his participation in scientific production and fulfilling the need of the society for scientific research, especially considering the spread of the coronavirus pandemic, with an average calculation of (4.20 - 4.35), and standard deviation (0.265 - 0.269).